The influence of Wordwall technology learning on the learning outcomes of the volleyball serve - Aktavia Putri Aisya; Bayu Budi Prakoso; Vega Candra Dinata; Moh. Fathur Rohman (Sriwijaya Journal of Sport, 2025)
Research Problems: Physical Education learning still faces challenges due to the use of conventional media such as blackboards, books, lectures, and skill demonstrations. As a result, students struggle to understand and practice volleyball serving techniques. To keep up with global developments, learning needs to utilize technology to become more innovative, adaptive, and responsive. Research Objective: This study aims to investigate the extent to which the use of Wordwall learning media as a supporting technology influences student learning outcomes in volleyball service material. Method: An experimental method was employed as the primary approach for this research, utilizing a Non-Randomized Control Group Pretest-Posttest Design. Sample selection implemented Cluster Random Sampling that yielded two groups: the first group consisted of 20 students from class XI-1 who served as the experimental group, while the second group included 20 students from class XI-4 who functioned as the control group. Results: The normality test results show that the data are normally distributed. Based on the Paired Sample T-Test, the Sig. (2-tailed) The value is 0.000 for both skill and knowledge aspects, indicating that the use of Wordwall as a learning medium has a significant effect on students’ volleyball serve learning outcomes. The Independent Sample T-Test also shows significance values of 0.002 for skills and 0.000 for knowledge, indicating a significant difference between the group using Wordwall and the group not using it. In addition, the improvement test shows an increase of 39% in the knowledge aspect and 44% in the skill aspect. Conclusion: The use of Wordwall learning media was proven to create a significant impact on improving student learning outcomes when studying volleyball service. As a learning medium that utilizes technology, Wordwall offers an appropriate option to support Physical Education teaching and learning activities conducted in schools.